Fiscal Effects of Minimum Wages – An Analysis for Germany - Thomas K. Bauer; Jochen Kluve; Sandra Schaffner; Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
Against the background of the current discussion on the introduction of statutory minimum wages in Germany, this paper analyzes the potential employment and fiscal effects of such a policy. Based on estimated labor demand elasticities obtained from a structural labor demand model, the empirical results imply that the introduction of minimum wages in Germany will be associated with significant employment losses that are concentrated among marginal and low- and semi-skilled full-time workers. Even though minimum wages will lead to increased public revenues from income taxes and social security benefits, they will result in a significant fiscal burden, due to increased expenditures for unemployment benefits and decreased revenues from corporate taxes.
Keywords: H60; J31; J88; 330; Minimum wages; employment; public budget; fiscal effects; Mindestlohn; Wirtschaftspolitische Wirkungsanalyse; Beschäftigungseffekt; Öffentliche Ausgaben; Öffentliche Einnahmen; Deutschland